LC-MS/MS analysis and biological activities of endemic Achillea sieheana Stapf from Türkiye - DİKPINAR, TUĞÇE; BİTİŞ, LEYLA (My University, 2022)
© 2022 Marmara University Press.In this study, in vitro ABTS, DPPH, 5-lipoxygenase, and α-glucosidase inhibitory activities of n-hexane (ASH), dichloromethane (ASD), ethyl acetate (ASE), and methanol (ASM) extracts from the aerial parts of endemic A. sieheana were assayed for the first time. The phytochemical content of ASE, the most active extract, has been first determined by LC-MS/MS. Also, the total amount of phenolic compounds of extracts were calculated. ASE demonstrated significant antioxidant activity with IC50 values of 0.096 and 0.156 mg/mL for ABTS and DPPH, respectively. ASD and ASE with IC50 values of 0.045 and 0.089 mg/mL exhibited significant anti-inflammatory activity. ASE showed moderate α-glucosidase inhibitory activity with an IC50 value of 0.774 mg/mL. Also, the total phenolic content was found to be highest in the ASE. Feruloylquinic acid, luteolin, luteolin glucoside, isorhamnetin, isovitexin, methoxyflavonoid like chrysoeriol and its glycoside derivative in the ASE were detected by LC-MS/MS. The results demonstrated that ASE had significant anti-inflammatory, antioxidant and moderate α-glucosidase inhibitory potential.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); A. sieheana; anti-inflammatory; antioxidant; LC-MS/MS; α-glucosidase